Ethics of Responsibility and Politics of Religion in the University; Analysis of the Document of the Islamic University - M.J. Emaeili (Taḥqīqāt-i Farhangī-i Īrān, 2019)
Over the last forty years, experts and researchers examining "impracticability," "immodesty," and "inefficiency" regarding religious policy in universities, have pointed to multiple causes and reasons Current research with respect to the role of the causes and reasons for this are considered Insignificant.  With the help of Weber's theory, the weakness of the "Ethics of responsibility" at the policy institution is brought to light Weber’s theory suggests that there is much suspicion, dissatisfaction, and opposition to Islamization On the other hand, in application to the failures of Islamization of universities in the weakness of morality, the policy of the institution bears responsibility.  The central question this article asks if religion policy in the university is based on the notion of "Responsibility Ethics.”  The author, with the main question and six sub- questions, makes a qualitative analysis of the Document of the Islamic University as approved by the Supreme Council of the Cultural Revolution of 1392 and will show that Religious policy in the university is not based on "Ethics of Responsibility.”  However, this requires another independent review as to whether the document is based on “Ethics of Belief” or not.